2000
DOI: 10.1007/bf03019006
|View full text |Cite
|
Sign up to set email alerts
|

Transfusions in patients undergoing cardiac surgery with autologous blood

Abstract: 705CAN J ANESTH 2000 / 47: 7 / pp [705][706][707][708][709][710][711] Purpose: Determinants of allogeneic blood use in cardiac surgery include preoperative factors such as female sex, age, body weight, hematocrit and red cell volume. We verified if these variables also predicted the need for allogeneic transfusions when autologous blood is predonated.Methods: Demographic and intraoperative variables, hemoglobin concentrations and transfusion requirements in patients undergoing cardiopulmonary bypass with autol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…[13] The present study demonstrated that the need for ABT was significantly reduced in the autologous transfusion group that underwent ANH.…”
Section: Discussionmentioning
confidence: 59%
“…[13] The present study demonstrated that the need for ABT was significantly reduced in the autologous transfusion group that underwent ANH.…”
Section: Discussionmentioning
confidence: 59%
“…[14][15][16][17]19,20,[22][23][24][25][26]28,[30][31][32][33][34]36,[38][39][40][41][42][43] This was followed by increasing age, which was found to be associated with a higher transfusion rate in 20 studies. 15,18,21,[23][24][25][26][27][28][29][30][31][32][33][38][39][40][41][42][43] Female gender and body size were also related to RBC transfusion in 15 studies 16,18,20,21,[24][25][26][29][30][31][32]36,[...…”
Section: Cardiac Surgerymentioning
confidence: 98%
“…27 Fourteen studies determined transfusion requirements in patients who had either elective or emergency cardiac surgery. [12][13][14]17,19,20,[22][23][24]29,31,35,36,38 Twelve studies examined patients who had both primary and reoperative surgery, 12,13,15,16,22,24,31,35,36,38,39,42 whereas 2 studies focused only on patients undergoing reoperative cardiac surgery. 21,34 Twelve studies were prospective cohort studies, [12][13][14]18,21,[25][26][27][28][29][30]43 and 3 were randomized controlled trials.…”
Section: Cardiac Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Aminocaproic acid and Tranexamic acid have frequent use too. 19 The Commonly used and avoiding Preoperative associated factors leading to postoperative bleeding are Clopidogrel which should be stopped five days before the surgery, Ticagrelor which should be stopped three days before the operation, Heparin for acute coronary syndromes, low molecular weight heparin and patients on Warfarin or novel oral anticoagulants as these factors are not analyzed in our study.…”
Section: Discussionmentioning
confidence: 99%